(untitled) (Veterinária Notícias, 2022)
A wide variety of microorganism species have been used as probiotics to improve the intestinal microbial balance, control and prevent the colonization of pathogenic bacteria and promote growth in animal production. Based on the various beneficial factors of probiotic agents, this study aimed to evaluate the effectiveness of three different formulations of probiotics strains through the analysis of antagonistic capacity against common pathogens from chickens gastrointestinal tract. Three formulations composed by Bacillus, Lactobacillus, Saccharomyces, Enterococcus, Bifidobacterium and Pediococcus were tested in vitro by the method of probiotic culture spot in plates seeded with inocula of Escherichia coli, Salmonella heidelberg and Campylobacter jejuni. The inhibition halos were measured and classified according to the degree of pathogenic bacteria inhibition. The formulation containing an association among Bacillus, Lactobacillus and Saccharomyces presented better results when compared to the other formulations.